Ignas Danilavičius and the Lithuanian Juridical Thought in the Beginning of the 19th Century - Vansevičius, Stasys (Problemos, 1969)
Under the conditions of the feudal-serfdom system the supporters of the bourgeois development made use of the ideas produced by the natural law school. The supporters of the old feudal regime took advantage of the theories originated by the reactionary historical school of law. I. Danilavičius treated critically the teachings of both law schools and was the initiator of progressive juridical thought in Lithuania. His statements concerning the nature of laws, his demands to provide equal rights to everybody, rights based on reason and justice, his criticism of serfdom reveal his democratic views. I. Danilavičius evaluated positively the French bourgeois revolution for the wreck of feudalism, for rendering the secular power independent from the ecclesiastic one, for granting all inhabitants equal rights. I. Danilavičius strove to liberate marriage and family from religious chains, demanding equality for husband and wife, between natural children and legal ones. I. Danilavičius looked upon the history of the Lithuanian society and law from the view-point of the natural law and drew rather radical conclusions.